Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Kepatuhan Mengkonsumsi Tablet Tambah Darah Di Wilayah Kerja Puskesmas Kuamang Kuning X Tahun 2023 - Haryanti, Dwi; Dayani, Dona Nopi; Lubis, Sunarti; Kencana, Dwike Cenderamata (Akademi Kebidanan Bunga Husada Samarinda, 2024)
The background to the problem of this research is to provide knowledge about the relationship between knowledge and attitudes of pregnant women with adherence to consuming Ferosus (Fe) tablets in the working area of ​​the Kuamang Kuning X Health Center. Based on an initial survey conducted by researchers at the Kuamang Kuning X Health Center, Bungo Regency, it was noted that most experienced anemia with an average Hb level below 10 gr percent. The results of interviews with 6 pregnant women about the importance of taking blood supplements regularly, it was found that 3 people knew the importance of taking blood supplements regularly, while 3 people did not know the importance of taking iron tablets regularly, because they did not know the importance of consuming iron tablets. The research design is analytic descriptive with a cross-sectional study method, namely collecting data at once (point time approach). The type of data in this study is to use primary data. The collection uses a research questionnaire. Based on the research, it was obtained that the majority of pregnant women had less knowledge, namely 25 respondents (41.7 percent). The majority of pregnant women have a positive attitude as many as 34 respondents (56.7 percent). The majority of Obedient Pregnant Women are as many as 36 respondents (60.0 percent). There is a relationship between Knowledge of Obedience of Pregnant Women in the Working Area of ​​the Kuamang Kuning Health Center with a significant value of ρ value equal to 0.000. There is a relationship between the attitudes and compliance of pregnant women in the working area of ​​the Kuamang Kuning health center with a significant value ρ value equal to 0.000